Constitutive modeling of dynamic recrystallization coupled to viscoplasticity. Issue 1 (25th January 2021) - Westermann, Hendrik; Mahnken, Rolf
Abstract: During thermomechanical processing the microstructure is subject to drastic changes. These changes relate to various physical mechanisms such as recrystallization, recovery, grain growth and phase transitions, heavily affecting material properties in engineering components. This enables the targeted adjustment of microstructures and the gradation of macroscopic mechanical properties. During thermomechanical processing the modeling of dynamic recrystallization is of major importance. Thus, we present a thermodynamically consistent framework based on an existing continuum mechanical model. Major improvements, including derived recrystallization volume fractions and clean distinction of true microstresses and nominal microstresses, have been made in comparison to the original model.